Correction: Liao et al. A Lightweight Cotton Verticillium Wilt Hazard Level Real-Time Assessment System Based on an Improved YOLOv10n Model. Agriculture 2024, 14, 1617 - Juan Liao; Xinying He; Yexiong Liang; Hui Wang; Haoqiu Zeng; Xiwen Luo; Xiaomin Li; Lei Zhang; He Xing; Ying Zang (Agriculture)
In the original publication [...]